Streaming in oscillatory flow through porous channels in thermoacoustics - Zaiham, Nur Afiqah Aina (2025)
Streaming in oscillatory flow of the alternative green technology known as thermoacoustics remains relatively less understood. The thermodynamic cycle in the system is driven by the oscillatory flow of the acoustic waves, understanding the nature of streaming, particularly within the porous structure of the system is crucial. Since the current study does not include a heat exchanger to generate a temperature gradient, it cannot directly be used as a complete thermoacoustic system. Instead, this design choice aligns with the primary aim of the study, which was to investigate the flow dynamics and acoustic streaming within an oscillatory flow field in a thermoacoustic system without thermal effect. This study was done using a parallel-plate porous channel operating under standing-wave conditions at a quarter wavelength. Both experimental and computational fluid dynamics (CFD) approaches were used. The experimental data, including the velocity, pressure and wall displacement were recorded under a resonance frequency of 23.6 Hz. The flow was maintained at room temperature and atmospheric pressure, with drive ratios ranging from 0.64% to 3.01%. These measurements were then incorporated into CFD simulations to provide deeper insight into complex flow physics. The two-dimensional (2D) CFD model was solved for minimum, medium and maximum flow conditions using the Shear Stress Transport (SST) k-Ï‰ turbulence model. Comparisons and discussions were made based on the data from the experiment, CFD and one-dimensional linear thermoacoustic theory. Results showed that the discrepancies between experimental and numerical results were slightly larger, possibly due to vibration effects during testing. To address this, a dynamic mesh was applied to simulate wall movement. This adjustment results in a slightly improved correlation with experimental data, especially for peak velocity at the downstream location. Further analysis of vortex structures over 20 phases of a flow cycle was carried out. The results show that under moving wall conditions, vortices shed further and extended longer into the open area, with a 12.40% deviation from the non-moving wall case at high acoustic amplitudes. The observation of flow streaming was made based on the progress of velocity profiles over time. In addition, the CFD model was extended with the Ffowcs-Williams and Hawkings (FW-H) acoustic model to analyse the sound pressure level (SPL) at three receivers positioned at the inlet, mid-channel and outlet of the computational domain. The highest SPL was recorded at the mid-channel, attributed to strong interactions between acoustic waves and solid boundaries, with the acoustic source positioned at the inlet. A parametric study using helium as the working fluid was also conducted to explore the effect of fluid properties on flow behavior and streaming. The simulations were conducted under the same drive ratios as those used for air. Results showed that Rayleigh streaming in helium is significantly weaker than in air, with a reduction in streaming intensity of approximately 34.17%, while Schlichting streaming appeared negligible. These findings were further strengthened by comparisons with existing literature, reinforcing the validity of the proposed methodology. Overall, this study provides new insights into nonlinear flow behavior in thermoacoustics. The findings enhance predictive modelling of oscillatory flows in porous channels and support the design of more efficient thermoacoustic systems for sustainable cooling, waste-heat recovery and renewable energy conversion.